The Impact of Eliminating a Child Benefit on Birth Timing and Infant Health - Cristina Borra; Libertad Gonzalez; Almudena Sevilla (Institute for the Study of Labor (IZA), 2014)
We study the effects of the cancellation of a sizeable child benefit in Spain on birth timing and neonatal health. In May 2010, the government announced that a 2,500-euro universal baby bonus would stop being paid to babies born on or after January 1st, 2011. We use detailed micro data from birth certificates from 2000 to 2011, and find that more than 2,000 families were able to anticipate the date of birth of their babies from (early) January 2011 to (late) December 2010 (for a total of about 9,000 births a week nationally). This shifting of deliveries led to a significant increase in the number of low birth weight babies, as well as a peak in neonatal mortality. These results suggest that announcement effects are important in shaping economic decisions and outcomes. They also provide new, credible evidence highlighting the negative health consequences of scheduling births for non-medical reasons.
Keywords: H00; H30; J00; J13; J17; 330; incentives; policy change; fertility; child health